RECONSTRUCTION OF HINDU PRIEST IN THE DYNAMICS OF THE INTER TRI SADHAKA AND SARWA SADHAKA IN BALI - Redana, Made; Wirawan, A.A. Bagus; Parimartha, I Gde; Anom Kumbara, A.A. Ngurah (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2019)
The reconstruction of Hindu Pandita in Bali marked a polarization of Hindu Pandita set in the difference of the clan (Soroh) and the belief system needs to be examined more deeply. The fact shows that there are still many Hindus who think that the Hindu Pandita belong to the Brahmin clan. This gap can be a stimulant misintensity against the issue of the Kapanditan and the condition to construct